Methadone versus buprenorphine with contingency management or performance feedback for cocaine and opioid dependence. - Schottenfeld, Richard S; Chawarski, Marek C; Pakes, Juliana R; Pantalon, Michael V; Carroll, Kathleen M; Kosten, Thomas R (The American journal of psychiatry, 2005)
Physicians may prescribe buprenorphine for opioid agonist maintenance treatment outside of narcotic treatment programs, but treatment guidelines for patients with co-occurring cocaine and opioid dependence are not available. This study compares effects of buprenorphine and methadone and evaluates the efficacy of combining contingency management with maintenance treatment for patients with co-occurring cocaine and opioid dependence.
Keywords: Adult; Analgesics, Opioid; Behavior Therapy; Buprenorphine; Cocaine-Related Disorders; Combined Modality Therapy; Comorbidity; Female; Humans; Male; Methadone; Opioid-Related Disorders; Substance Abuse Detection; Token Economy; Treatment Outcome